Eficiência nos gastos de instituições federais de ensino superior: uma análise envoltória de dados - Oliveira, Nelize Aparecida de (2016)
The role of the public budget is the maximization of social welfare. The efficient allocation of public resources is essential for achieving this goal. In this sense the Federal Universities should manage their budget efficiently to make the most with the least possible consumption. The objective of the research is to investigate the efficiency in spending of Federal Institutions of Higher Education. The method used was a data envelopment analysis (DEA). For the model we used information of expenditures of federal institutions of higher education in 2013, as well leaf university rank for the same year. The results show that four institutions are at the frontier of efficiency in spending: UFAL; UFPE; UFU; and UFS. On the other hand, the UFG, the UFRR the UFTM and UFERSA were classified as the most inefficient, being inverted on the border of efficiency. The model also shows the clearances or waste for each institution and the influence (benchmark) that some institutions have on others.